2018
DOI: 10.3390/ma11050679
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of PVA Alkaline Solid Polymer Electrolyte with Addition of Bamboo Charcoal

Abstract: Natural bamboo charcoal (BC) powder has been developed as a novel filler in order to further improve performances of the polyvinyl alcohol (PVA)-based alkaline solid polymer electrolyte (ASPE) by solution casting method. X-ray diffraction patterns of composite polymer electrolyte with BC revealed the decrease in the degree of crystallinity with increasing content of BC. Scanning electron microscopy images showed pores on a micrometer scale (average diameter about 2 μm) distributed inside and on the surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 35 publications
(47 reference statements)
1
33
0
2
Order By: Relevance
“…In the previous work, it was indicated that Cu(II)-complex improved the amorphous structure in the PVA-composed system [ 14 ]. According to previous report [ 71 ], the growth in the structure of amorphous is useful in local chain segmental movement because it promotes the transportation of ions and thus enhances the σ DC . Thus, ions transfer freely through the PE.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous work, it was indicated that Cu(II)-complex improved the amorphous structure in the PVA-composed system [ 14 ]. According to previous report [ 71 ], the growth in the structure of amorphous is useful in local chain segmental movement because it promotes the transportation of ions and thus enhances the σ DC . Thus, ions transfer freely through the PE.…”
Section: Resultsmentioning
confidence: 99%
“…These functional groups are substantial for mixing with conducting salt and a filler. The utilization of PVA as substantive material as a host polymer for electrolyte was reported earlier [ 12 ].…”
Section: Introductionmentioning
confidence: 95%
“…The high ionic conductivity was attributed to the amorphous structure of the film and ability to maintain the hydration of (SO 4 ) 2− ions . Despite all these developments, the conductivities of these neutral pH ion‐conducting polymer electrolytes are still below those reported in many proton and hydroxide‐conducting electrolytes …”
Section: Introductionmentioning
confidence: 99%